Optimizing HIV Investments in Armenia - World Bank (World Bank, Washington, DC, 2016)
This report summarizes the findings of an allocative efficiency analysis on Armenia`s national HIV epidemic and response conducted in 2014-15. The report addresses core questions for resource allocation such "How can HIV funding be optimally allocated to the combination of HIV response interventions that will yield the highest impact?" or "What level of investment is required to achieve national targets, if we allocate resources optimally?". The report describes epidemiological and HIV financing trends as well as identifies sub-populations, which are most affected by the epidemic. Based on this information, the optimized mix of interventions for minimizing new HIV infections and deaths is identified using mathematical modelling techniques. Required investments into programs for key populations and antiretroviral treatment are established and translated into policy recommendations. The AE analysis indicates that, using the same US 3.9 million dollars of annual programmatic HIV spending recorded in 2013, Armenia could avert an additional 290 new HIV infections and 288 AIDS-related deaths from 2015 to 2020 if these resources were allocated optimally to minimize both HIV incidence and AIDS-related deaths.